Far upstream element binding protein 1 binds the internal ribosomal entry site of enterovirus 71 and enhances viral translation and viral growth - Huang, Peng-Nien (Oxford University Press, 2011)
Enterovirus 71 (EV71) is associated with severe neurological disorders in children, and has been implicated as the infectious agent in several large-scale outbreaks with mortalities. Upon infection, the viral RNA is translated in a cap-independent manner to yield a large polyprotein precursor. This mechanism relies on the presence of an internal ribosome entry site (IRES) element within the 5′-untranslated region. Virus–host interactions in EV71-infected cells are crucial in assisting this process. We identified a novel positive IRES trans-acting factor, far upstream element binding protein 1 (FBP1). Using binding assays, we mapped the RNA determinants within the EV71 IRES responsible for FBP1 binding and mapped the protein domains involved in this interaction. We also demonstrated that during EV71 infection, the nuclear protein FBP1 is enriched in cytoplasm where viral replication occurs. Moreover, we showed that FBP1 acts as a positive regulator of EV71 replication by competing with negative ITAF for EV71 IRES binding. These new findings may provide a route to new anti-viral therapy.